Sponge (Porifera) species from the Mediterranean coast of Turkey (Levantine Sea, eastern Mediterranean), with a checklist of sponges from the coasts of Turkey - Evcen, A.; Çinar, M.E. (Turkish Journal of Zoology,, 2012)
Th e present study deals with sponge species collected along the Mediterranean coast of Turkey in 2005. A total of 29 species belonging to 19 families were encountered, of which Phorbas plumosus is a new record for the eastern Mediterranean, 8 species are new records for the marine fauna of Turkey (Clathrina clathrus, Spirastrella cunctatrix, Desmacella inornata, Phorbas plumosus, Hymerhabdia intermedia, Haliclona fulva, Petrosia vansoesti, and Ircinia dendroides), and 19 species are new records for the Levantine Sea (C. clathrus, Sycon raphanus, Erylus discophorus, Alectona millari, Cliona celata, Diplastrella bistellata, Mycale contareni, Mycale cf. rotalis, Mycale lingua, D. inornata, P. plumosus, Phorbas fi ctitius, Lissodendoryx isodictyalis, Hymerhabdia intermedia, H. fulva, P. vansoesti, I. dendroides, Sarcotragus spinosulus, and Aplysina aerophoba). Th e morphological and distributional features of the species that are new to the Turkish marine fauna are presented. In addition, a check-list of the sponge species that have been reported from the coasts of Turkey to date is provided.